The financing of local government in China: Stimulus loan wanes and shadow banking waxes - Chen, Zhuo; He, Zhiguo; Liu, Chun (Journal of Financial Economics, 2020)
The upsurge of shadow banking is typically driven by rising financing demand from certain real sectors. In China, the 4 trillion yuan stimulus package in 2009 was behind the rapid growth of shadow banking after 2012, expediting the development of Chinese corporate bond markets in the poststimulus period. Chinese local governments financed the stimulus through bank loans in 2009 and then resorted to nonbank debt financing after 2012 when faced with rollover pressure from bank debt coming due. Cross-sectionally, using a political-economy-based instrument, we show that provinces with greater bank loan growth in 2009 experienced more municipal corporate bond issuance during 2012–2015, together with more shadow banking activities including trustloans and wealth management products. China’s poststimulus experience exhibits similarities to financial market development during the US National Banking Era.